Use what we can linear cominations to eliminate one variable.
Start with your equations, but you multiply in a factor c for one of them.
c(\Lambda-2)x+cy=0
x+(\Lambda-2)y=0
And add them up:
(c(\Lambda-2)+1)x+(c+\Lambda-2)y=0
Now we see that if we put in
c=2-\Lambda
Then the combined equation has only x not y. We eliminate y with that choice:
((2-\Lambda)(\Lambda-2)+1)x=0
Then we have
(-\Lambda^2+4\Lambda-3)x=0
We can factor that:
-(\Lambda-1)(\Lambda-3)x=0
So we have one of the following:
x=0, \Lambda=1, \Lambda=3
Suppose x=0. Then your original equations become:
y=0
(\Lambda-2)y=0
They both have the same solution y=0, but x=y=0 is just the trivial solution. That did not work. In most cases setting a variable to zero does not work; you need to get the right value for your parameter, in this case \Lambda, instead. That's what the other two possibilities we got from the linear combination are designed to do.
So try \Lambda=1 next.
(-1)x+y=0
x+(-1)y=0
We see now that instead of just x=y=0, we have solutions with x=y for any value of x or y. Thus \Lambda=1 does give nontrivial solutions.
Finally try \Lambda=3. You can work out that with this value of \Lambda both of your original equations become x+y=0. Again we get nontrivial solutions, this time with y=-x.